The influence of initial roughness and circular axial run-out on friction and wear behavior of Si3N4–Al2O3 sliding in water. (September 2016) - Balarini, R.; Strey, N.F.; Sinatora, A.; Scandian, C.
Abstract: Recently, it has been shown that water-lubricated sliding of Si3 N4 against Al2 O3 can result in steady-state friction coefficient values as low as 0.004. However, most experiments were performed using extremely polished surfaces and did not consider the effect of circular axial run-out of the discs, which could be important in practical applications. In this paper it was investigated the influence of these parameters on the ultra-low friction coefficient (ULFC) phenomenon, including correlations with running-in. Greater initial surface roughness and circular axial run-out resulted in greater running-in duration and wear. In addition, the transition of wear mode from mechanical to tribochemical dominated as a function of sliding distance was clarified and it was proposed that a mixed lubrication regime is required for ULFC to occur. Highlights: ULFC regime was reached during water-lubricated ball-on-disc tests of Si3 N4 against Al2 O3 . Greater initial surface roughness and circular axial run-out results in extended running-in duration. ULFC regime was observed only when silicon concentration in lubricating water was above a 1.3 mg/L. Material tranfered from Si3 N4 forms an uneven tribofilm on the alumina surface, smoothing it.